Cruelty - Dahl, Roald (London : Penguin, 2017)
From Roald Dahl, the master of the sting in the tail, a newly collected audiobook of his darkest stories, read by Will Self, Adrian Scarborough, Stephanie Beacham, Andrew Scott, Richard E Grant, Tamsin Greig, Mark Heap, Juliet Stevenson and Jessica Hynes. 'Cruelty has a human heart . . .' Even when we mean to be kind we can sometimes be cruel. We each have a streak of nastiness inside us. In these ten tales of cruelty master storyteller Roald Dahl explores how and why it is we make others suffer. Collected together for the first time, stories include The Great Automatic Grammatizator, Royal jelly, Mrs Bixby and the Colonel's Coat,The Swan, Poison, Skin, The Princess and the Poacher, Genesis and Catastrophe and Mr Feasey. Dahl understood our deepest secrets, desires and fears and Cruelty is one of four books - the rest being Lust, Deception and Madness - that explore our hidden selves.
Keywords: English fiction -- 20th century. -- Cruelty -- Fiction. -- Cruelty. -- English fiction